Ancient polymorphism within hylarana signata (amphibia: anura: Ranidae) lineages of west (peninsular) and east (Sarawak, Borneo) Malaysia - Ramlah, Zainudin; Badrul Munir, Md Zain; Shukor, Md Nor; Mustafa, Abdul Rahman; Norhayati, Ahmad (2009)
The Hylarana signata group in Malaysia, as currently construed, comprises two species- Hylarana signata and H. picturata. Both are similar in morphology and habits, but differ in colouration (chiefly, the presence or absence of a dorsolateral line). It has been suggested recently that Malaysian H. signata (from both Peninsular and Borneo) is different from H. signata of Philippines and may be non-conspecific, also from what is currently referred to this taxon on Malaysian Borneo. Specimens of the Hylarana signata group were sequenced to detect genetic variation among species and to confirm the existence of cryptic species, via 16S rRNA gene. Seven study sites in Sarawak were chosen for data collection, namely four National Parks (Matang/Matang, Bako, Mulu and Similajau), and three unprotected areas (Borneo Heights, Sadong Jaya and Bario). Data from Tasik Chini, Pahang, West (Peninsular) Malaysia were included in our molecular analysis, to infer relationships within the species group. PCR amplification and direct sequencing of partial 16S rRNA mitochondrial DNA was used to infer the phylogeny presented. The study revealed phylogenetic complexity within Malaysia Hylarana signata group due to the occurrence of cryptic species or ancient polymorphism of the lineages. The results obtained underscore the need for a complete sequence of DNA regions or multigenes of the same rate of evolution in order to elucidate the phylogenetic relationship in the group through more extensive samplings spanning wider geographical ranges.